Genomic signatures of inbreeding and mutation load in a threatened rattlesnake. Issue 21 (9th September 2021) - Ochoa, Alexander; Gibbs, H. Lisle
Abstract: Theory predicts that threatened species living in small populations will experience high levels of inbreeding that will increase their genetic load, but recent work suggests that the impact of load may be minimized by purging resulting from long‐term population bottlenecks. Empirical studies that examine this idea using genome‐wide estimates of inbreeding and genetic load in threatened species are limited. Here we use individual genome resequencing data to compare levels of inbreeding, levels of genetic load (estimated as mutation load) and population history in threatened Eastern massasauga rattlesnakes ( Sistrurus catenatus ), which exist in small isolated populations, and closely related yet outbred Western massasauga rattlesnakes ( Sistrurus tergeminus ). In terms of inbreeding, S . catenatus genomes had a greater number of runs of homozygosity of varying sizes, indicating sustained inbreeding through repeated bottlenecks when compared to S . tergeminus . At the species level, outbred S . tergeminus had higher genome‐wide levels of mutation load in the form of greater numbers of derived deleterious mutations compared to S . catenatus, presumably due to long‐term purging of deleterious mutations in S . catenatus . In contrast, mutations that escaped species‐level drift effects within S . catenatus populations were in general more frequent and more often found in homozygous genotypes than in S . tergeminus, suggesting a reduced efficiency of purifying selection in smaller S . catenatus populations for most mutations. Our results support an emerging idea that the historical demography of a threatened species has a significant impact on the type of genetic load present, which impacts implementation of conservation actions such as genetic rescue.